Human Development and Economic Growth - Gustav Ranis (Yale University, Economic Growth Center, 2004)
Recent literature has contrasted Human Development, described as the ultimate goal of the development process, with economic growth, described as an imperfect proxy for more general welfare, or as a means toward enhanced human development. This debate has broadened the definitions and goals of development but still needs to define the important interrelations between human development (HD) and economic growth (EG). To the extent that greater freedom and capabilities improve economic performance, human development will have an important effect on growth. Similarly, to the extent that increased incomes will increase the range of choices and capabilities enjoyed by households and governments, economic growth will enhance human development. This paper analyzes these relationships and the two-way linkages involved.
Keywords: O15; O11; 330; Economic Growth; Human Development; Wirtschaftswachstum; Entwicklungsindikator